Electromechanical energy conversion - Gourishankar, Vembu (Internatinal Texbook Co, 1965)
Contents: Chapter 1: The Magnetic Circuit Concept Chapter 2: Direct- Current Excitation of Ferromagnetic Struc-tures Chapter 3: Alternating - Current Excitation of Ferromagnetic Structers Chapter 4: Tranformers Chapter 5: Mechanical Forces in Magnetic Systems Chapter 6: Dynamic Equations of Linear Electrical and Mechan-ical Systems Chapter 7 : Graphical Representation of Electromechanical Sys-tems